2012
DOI: 10.1007/s12072-012-9345-8
|View full text |Cite
|
Sign up to set email alerts
|

B cell-activating factor is associated with the histological severity of nonalcoholic fatty liver disease

Abstract: Nonalcoholic steatohepatitis patients had higher levels of serum BAFF than patients with SS, and higher levels were associated with the presence of hepatocyte ballooning and advanced fibrosis. The serum BAFF level may be a useful tool for distinguishing NASH from SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 44 publications
0
35
2
Order By: Relevance
“…14 The present data seem to be inconsistent with those of our previous study. However, Bigorgne et al 32 showed that steatosis increases lymphocyte recruitment to the liver.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…14 The present data seem to be inconsistent with those of our previous study. However, Bigorgne et al 32 showed that steatosis increases lymphocyte recruitment to the liver.…”
Section: Discussioncontrasting
confidence: 99%
“…We previously showed that BAFF impairs insulin sensitivity and is associated with NAFLD severity, 13,14 indicating that this molecule is an important factor in lipid and glucose metabolism. In this study, as expected, HFD-fed BAFF-R À / À mice showed lower body weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that treatment with recombinant BAFF protein impaired insulin-mediated glucose uptake in 3T3-L1 adipocytes. BAFF plasma levels were significantly correlated with body fat and dietary composition in obese CentralEuropean Caucasian individuals [5], and the levels were also observed to be significantly higher in Japanese patients with nonalcoholic fatty liver disease [6].…”
Section: Introductionmentioning
confidence: 89%
“…Meanwhile, approximately 20-30% of patients with NAFLD, which is characterized by obesity, insulin resistance and other excessive nutritional intake, had ANA in their sera, suggesting that the autoimmune response might be involved in the process of insulin resistance [62][63][64][65]. The elevation of serum B-lymphocyte activating factor (BAFF) levels in patients with nonalcoholic steatohepatitis (NASH) may be attributed to insulin resistance [66].…”
Section: Autoantibodies In Sera Of Patients With Liver Disease Associmentioning
confidence: 99%